The Influence of Customer Experience Through Product Publication on Alfagift Service Quality - Junisha, Anggi Deafita; Tambunan, Resman Muharul (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
Retail companies in the digital era must continue to innovate to improve customer experience and service quality. This study aims to analyze the effect of customer experience on service quality through product publications on the Alfagift application. Employing a quantitative approach, this study uses Structural Equation Modeling - Partial Least Squares (SEM-PLS) to analyze data from 150 Alfagift users in Limo District, Depok City. The results showed that customer experience significantly affected service quality (β = 0.565, p < 0.05), indicating that positive experiences increase customer perceptions of service quality. In addition, customer experience also significantly impacted product publications (β = 0.818, p < 0.05), stating that well-managed experiences result in more effective product communication. Product publications act as a mediating variable that strengthens the relationship between customer experience and service quality (β = 0.251, p < 0.05). These findings support the Customer Experience and Service Quality Theory (SERVQUAL) and enrich digital marketing studies. The practical implication of this study is that Alfamart needs to optimize its product publication strategy to increase customer engagement and strengthen service quality.